FROM STATE OWNERSHIP TO MODERN CORPORATIONS: ANALYSIS OF REGULATIONS AND PRINCIPLES OF STATE-OWNED ENTERPRISE GOVERNANCE IN BALANCING DEVELOPMENT FUNCTIONS AND PROFITABILITY IN THE ERA OF ECONOMIC GLOBALISATION - Gunawan Widjaja (CV. Adiba Aisha Amira, 2026)
This article analyses the transformation of State-Owned Enterprises (SOEs) from bureaucratic state-owned entities into professional and competitive modern corporations in the era of economic globalisation. The main focus of the study is on the regulations governing the status and role of SOEs, particularly Law No. 19 of 2003 and its amendments, as well as the application of good corporate governance principles in maintaining a balance between national development functions and profit generation. The analysis shows that the separation of functions between the government as owner and SOEs as operators, the professionalisation of management, and the strengthening of supervisory mechanisms are key to overcoming the tensions caused by the dual mandate of SOEs. However, political challenges, policy intervention, and social obligations that are not managed transparently still hinder performance optimisation. This article concludes that SOEs can function as modern state corporations based on public values if regulations, governance, and organisational culture are designed synergistically to maintain a balance between public and market interests.